Internal And external factors influencing the adoption of ICTs in cultural sector companies: : Bolívar, Colombia - Armirola Garcés, Ledy Paola
The permanent changes that information and communication technologies (ICT) have brought to business management have had a considerable impact on the adoption of technologies in companies. This article presents a research conducted in companies in the cultural area of the department of Bolivar in Colombia, which sought to understand the internal and external factors that influence the adoption of technology. It is a qualitative study in which in-depth interviews were conducted with 21 companies before and after the Covid-19 pandemic, in order to understand the perspectives and situations that have influenced the technology adoption process. The results show that companies are willing to adopt technologies, are aware of their importance and value ICTs as useful tools for their business and communication management. However, there are barriers to adoption associated especially with costs and the use of technology.